Pleiotropic effects of antibiotics on T cell metabolism and T cell-mediated immunity - Franz, Tobias; Negele, Jonas; Bruno, Philipp; Böttcher, Martin; Mitchell-Flack, Marisa; Reemts, Lea; Krone, Anna; Mougiakakos, Dimitrios; Müller, Andreas J.; Zautner, Andreas E.; Kahlfuss, Sascha (Frontiers in Microbiology, 2022)
T cells orchestrate adaptive and innate immune responses against pathogens and transformed cells. On the other hand, T cells are the main adaptive effector cells that mediate allergic and autoimmune diseases. Within the last years, it became clear that activation, differentiation, effector function, and environmental adaption of T cells is closely linked to their energy metabolism. Beyond the provision of energy equivalents, metabolic pathways in T cells generate building blocks needed for clonal expansion. Further, metabolic intermediates were shown to directly serve as source for epigenetic gene regulation by histone and DNA modification mechanisms. To date, several antibiotics were demonstrated to modulate the metabolism of T cells especially by altering mitochondrial function. We here set out to systematically review current evidence how beta-lactam antibiotics, macrolides, fluoroquinolones, tetracyclines, oxazolidinones, nitroimidazoles, and amphenicols alter the metabolism and effector function of CD4+ T helper cell populations and CD8+ T cells. Based on this evidence, we develop an overview how the usage of these antibiotics may be beneficial or detrimental in T cell-mediated physiological and pathogenic immune responses by altering the metabolism of different T cell populations.